Efecto de los áfidos Metopolophium dirhodum (Walk), Rhopalosiphum padi (L.) y Sitobion avenae (Fab.) sobre el desarrollo de la parte aérea y radicular del trigo - Kramm, V (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The effect of ariruliferons aphids M. dichodum, R padi and S avenae on the development of roots and aerial parts, was tested on Triticum aestivum L. or Express, sown in pots. Wheat plants were infested with first instar aphids in number of three, ten and thirty by axis, at the stages 2-3, 5-6 and 8-9 of the Feekes'scale respectively. The aphids were killed when the plants were af stages 10.1 to 10.5 of scale. Aphids affected significantly root dry weight, and the aerial part dry weight root weight ratio. The effect of the different aphid's species on the root dry weight was similar. Aphids did not affect, significantly, the aerial part dry weight, number of tiller's height, flag leaf sheath area, number of leaves per plant and number of spikes per head.